Analisis Kandungan Selulosa Tumbuhan Kiambang (Salvinia Molesta) dengan Metode Wendee-Chesson-Datta: Analysis of Cellulose Content of Kiambang Plants (Salvinia molesta) Using the Wendee-Chesson-Datta Method - Muzayyanah, Nana; Syauqi, Ahmad; Ramadhan, Majida (Jurnal SAINS ALAMI (Known Nature), 2024)
The Salvinia molesta plant is classified as a nuisance and is found in waters. In a good-quality environment, the growth of Salvinia molesta can increase rapidly. Their growth causes light to be unable to enter the waters, and the ecosystem is disrupted until it does not work. The constituent elements of the Salvinia molesta body are cellulose in the cell walls and can be used as animal feed, fuel and alternative energy sources. The utility of Salvinia molesta can reduce the population density, so that disturbances in the aquatic ecosystem can also be reduced. The study aims to quantitatively analyze cellulose in floating and sinking leaves following the Wendee and Cheson-Datta methods. The stages carried out are extracting fiber and determining the cellulose fraction. The results of the analysis of cellulose in sinking and floating leaves have average values ​​of 25.5 ± 2.41% and 18.2 ± 5.85%, respectively. Based on the independent t-test, the average percentage of cellulose did not have a significant difference or was not statistically significant because it had a p-value of 0.084 (p>0.05). Keywords: Kiambang, Salvinia molesta, Cellulose, Wendee-Chesson-Datta Abstrak Tumbuhan kiambang (Salvinia molesta) digolongkan sebagai jenis pengganggu dan berada diperaian. Pada lingkungan dengan kualitas baik, pertumbuhan kiambang dapat mengalami peningkatan pesat. Pertumbuhan mereka menyebabkan cahaya tidak dapat masuk ke perairan dan ekosistem terganggu hingga tidak bekerja Unsur penyusun tubuh kiambang adalah selulosa berada dalam dinding sel dan dapat dimanfaatkan sebagai pakan ternak, bahan bakar dan sumber energi alternatif. Pemanfaatan kiambang dapat mengurangi kepadatan populasinya, sehingga gangguan pada ekosistem perairan juga dapat dikurangi. Penelitian mempunyai tujuan analisis kuantitatif selulosa pada daun mengapung dan tenggelam mengikuti metode Wendee dan chesson- datta. Tahap yang dilaksanakan adalah mengekstrak serat dan penentuan fraksi selulosa. Hasil analisis selulosa pada daun tenggelam dan mengapung memiliki nilai rata-rata masing-masing sebesar 25.5 ± 2,41 % dan 18.2 ± 5,85 %. Berdasarkan uji independent t-test, rerata persen selulosa tidak terdapat perbedaan bermakna atau tidak signifikan secara statistik karena memiliki p-value 0,084 (p>0,05). Kata kunci: Kiambang, Salvinia molesta, Selulosa, Wendee-Chesson-Datta